Test-retest reliability of postural sway on foam and natural rubber pads in healthy adults - Boonkerd, Chuanpis; Archasawat, Yatiga; Sertkhamsorn, Wachiraporn; Saensanoh, Panida; Laddawong, Teerapat; Kitsuksan, Thanawat (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. Postural control is essential for humans to maintain balance under both static and dynamic conditions. A variety of unstable support surfaces are used to evaluate postural control. Balance foam pads are relatively expensive, whereas natural rubber pads use a natural material with equivalent viscoelastic properties that are inexpensive and widely available. No postural sway and reliable data existed to support the practice of using a natural rubber pad. The purposes of the study were to determine the test-retest reliability of postural sway by using a natural rubber pad and to compare postural sway in healthy adults while using a foam pad, a natural rubber pad and a ﬁrm surface.Methods. Nineteen healthy participants were measured for centre of pressure (COP) velocity and displacement during a quiet stance, with their eyes closed, on a balance foam pad (blue foam – Airex®), a natural rubber pad and a ﬁrm surface on a force platform. Two repeated sessions were conducted three days apart. Intraclass correlation coeﬃcients were used to determine the test-retest reliability. A one-way repeated measures ANOVA was used to compare the three surface conditions.Results. The natural rubber pad demonstrated moderate to good reliability for COP velocity and COP displacement. Also, there were no signiﬁcant diﬀerences in anteroposterior (AP) and mediolateral (ML) COP velocity and displacement between the balance foam pad and the natural rubber pad.Conclusions. Our ﬁndings indicate that a natural rubber pad could be employed as a low-cost alternative to the balance foam pad for evaluating the balance of healthy adults.
Keywords: postural sway; reliability; natural rubber pad